Music therapy in hemodialysis patients: Systematic review and meta-analysis - Feng Lin; Long Chen; Yin Gao (Elsevier, 2024)
Background: Patients undergoing hemodialysis (HD) face significant challenges; however, non-pharmaceutical interventions hold potential for enhancing their quality of life. This paper evaluates the effects of music therapy on various mental and physiological outcomes in patients undergoing HD. Methods: This systematic review and meta-analysis followed the PRISMA 2020 guidelines. A comprehensive database search conducted up to May 21, 2024, identified studies for inclusion based on PICOS criteria. The methodological quality of these studies was assessed using the Cochrane risk-of-bias tool and Review Manager 5.4. For the meta-analysis, R and Stata/SE 15.1 were used, applying a random-effects model in cases of significant heterogeneity, and a fixed-effects model when heterogeneity was minimal. Results: Twenty-four studies involving 1703 participants were analyzed. Music therapy significantly decreased anxiety (SMD: −0.72, 95 % CI: −0.97 to −0.46, I²: 83 %), pain (SMD: −1.22, 95 % CI: −1.68 to −0.75, I²: 93 %), depression (SMD: −0.85, 95 % CI: −1.31 to −0.39, I²: 77 %), stress (SMD: −0.93, 95 % CI: −1.17 to −0.68, I²: 41 %), and adverse reactions associated with HD (SMD: −0.67, 95 % CI: −0.88 to −0.46, I²: 0 %), all showing strong effect sizes (p < 0.001 for all). However, no significant changes were observed in sleep quality, fatigue, satisfaction with HD, systolic or diastolic blood pressure, heart rate, or finger temperature. A slight reduction in respiration rate (p = 0.0072) and an increase in oxygen saturation (p = 0.0056) were noted. While music therapy showed promising results, the notable heterogeneity in pain and anxiety outcomes suggests careful interpretation, although no significant publication bias was detected. Conclusion: Music therapy has demonstrated encouraging outcomes in improving the well-being of patients undergoing HD, particularly in reducing anxiety, pain, and stress. However, due to notable heterogeneity and methodological issues such as small sample sizes and inconsistent blinding, further high-quality research is needed to confirm these findings and establish more robust evidence.